The value of sST2 in risk stratification and short-term prognosis of acute pulmonary embolism: a pilot study focusing on intermediate-risk subgroups - Wang, Jian; Liu, Zhen; Jiao, Yan; Cheng, Yanli; Li, Jinlong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIntermediate-risk acute pulmonary embolism (APE) represents a heterogeneous group that is temporarily hemodynamically stable and still has a high mortality. The aim of this study was to assess the predictive value of soluble growth stimulation expressed gene 2 (sST2) in risk stratification and short-term prognosis in this group.MethodsThis retrospective observational study included 128 patients with intermediate-risk APE between February 2020 to November 2023. Univariate or multivariate analysis were carried out for exploring the associations of sST2 with risk stratification and adverse event. Univariate logistic regression analysis and characteristic curve (ROC) were performed.ResultsCompared with the intermediate-low risk group, higher sST2 level (25.8 ng/ml vs. 11.5 ng/ml, P < 0.001) and more adverse events (28.2% vs. 8%, P = 0.006) were observed in the intermediate-high risk group. Univariate logistic regression analysis showed that sST2 was associated with higher risk stratification (OR = 1.085, 95%CI 1.042–1.129, P < 0.001) and adverse events (OR = 1.049, 95%CI 1.027–1.072, P < 0.001). For intermediate-high risk stratification prediction, the AUC (area under the curve) was 0.754 (95% CI: 0.671–0.837, P < 0.001) using sST2 and the optimal probability of cut-off value was 16.20 ng/ml. For adverse events prediction, the AUC was 0.832 (95% CI 0.751–0.913; P < 0.001), while the optimal cut-off value was 16.20 ng/ml.ConclusionssST2 is associated with risk stratification and poor short-term prognosis for intermediate-risk APE, and it is a promising new biomarker that may contribute to further stratification for intermediate-risk subgroups and identification of individuals with a propensity to develop adverse events during hospitalization.